Surgical approach to chronic subdural hematoma: review of pathophysiology and experience at our center - Romero Vinet, Hugo; Horlacher, Edoardo; Bennett, Carlos (Revista Argentina de Neurocirugía, 2026)
Background: chronic subdural hematoma (cSDH) is a common neurosurgical entity in older adults, characterized by persistent inflammation of a neomembrane with fragile neovascularization and episodes of recurrent microhemorrhage. Despite standard surgical management using burr hole and subdural drainage, symptomatic recurrence rates remain high, reaching up to 20% in some series. Objectives: to evaluate clinical efficacy and recurrence rates associated with a subperiosteal drain with a wide subgaleal pocket in patients undergoing surgery for cSDH at a tertiary center. Methods: this was a retrospective study including 213 adult patients who underwent evacuation of cSDH using burr hole and subperiosteal drainage. Clinical, surgical, and short- and medium-term follow-up variables were analyzed. Results: the mean age was 69.6 years; 67.4% were men. The most common symptom was motor deficit (73.71%), followed by sensory disturbance (52.58%). A single trephine was used in 81.22% of cases. Drain removal was performed within the first 48 hours in 89.11% of patients. The rate of symptomatic recurrence requiring reintervention was 3.37%, markedly lower than that reported in traditional series with subdural drains. Conclusions: a subperiosteal drainage with a wide subgaleal pocket showed excellent clinical results: low recurrence rate, rapid recovery, and minimal complications. The technique proved effective even in patients with comorbidities and on anticoagulant therapy.